An Empirical Analysis of the Relationships Among Third Sector, State and Market in Brazil and Portugal - Melo, Marina Félix (Revista de Ciências Sociais, 2017)
This article aims to bring the discussion of the relationship between Non-Governmental Organizations (NGOs) and other sectors: the State and the Market. The proposal is based on four case studies conducted between 2008 and 2013 in Brazil, and 2010 and 2012 in Portugal. This study had investigated the institutional professionalization of these entities, considering aspects such as autonomy of NGOs, maintaining networks cooperation, labor relations and others analytical dimensions that relate to the relationship between the three sectors. We conducted the following pages with the presentation and analysis of this empirical study, with a contextualization of the cases followed from the sociology of organizations.